Interactive Governance and Actor Diversity in Religious Conflict Prevention: A Case Study of Makassar City, Indonesia - Ansyar, ‎; Sukri, ‎; Abdullah, Suparman; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
This study examines the diversity dimension of interactive governance in religious conflict prevention in Makassar City, Indonesia, which experiences 70.2% of all conflicts in South Sulawesi. The research analyzes four critical variables: actors and interest groups, values and interests, levels of engagement, and resources in governance systems. Through qualitative methodology involving interviews with key stakeholders from law enforcement, religious institutions, and government agencies, this study identifies how actor diversity influences governance effectiveness. Findings reveal a complex ecosystem where the Forum for Religious Harmony (FKUB) functions as the primary institution facilitating dialogue, complemented by government agencies, religious organizations, law enforcement, and grassroots initiatives. The integration of local wisdom principles, such as “Makassar Sikatutui” with formal governance mechanisms provides cultural foundations for religious harmony. The governance system demonstrates multi-layered engagement extending from city-level institutions to neighborhood communities, with decision-making bodies balancing proportional representation with inclusive participation. While innovative programs have mobilized significant human resources with 1340 “Agents for Strengthening Community Harmony,” financial resources remain limited despite government’s allocation of 500 million rupiah for harmony programs. The research demonstrates that effective governance of religious diversity depends on accommodating diverse actors and interests, integrating cultural values with formal mechanisms, establishing multilevel engagement structures, and mobilizing varied resource types. This contributes to understanding how diversity management within governance systems can enhance religious conflict prevention in complex urban environments.